2016
DOI: 10.1111/jbg.12223
|View full text |Cite
|
Sign up to set email alerts
|

Traditional livestock breeding practices of men and women Somali pastoralists: trait preferences and selection of breeding animals

Abstract: This is an open access article under the terms of the Creative Commons AttributionNonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. SummarySomalia, one of the world's poorest countries, has livestock as the mainstay of the economy, with an estimated 65% of the population engaged in the livestock sector. This paper presents a gendered study on the traditional live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 11 publications
5
27
0
Order By: Relevance
“…This present information may inform breeding management decisions along gender mainstreaming in the study localities. In a related study in other species, Marshall et al (2016) reported that gender differences may result from production objectives and the specific roles and responsibilities of males and females in traditional livestock rearing. This is linked to the constant state of change, evolution and development of traditional gender roles (Paudel et al 2009;Karmebäck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This present information may inform breeding management decisions along gender mainstreaming in the study localities. In a related study in other species, Marshall et al (2016) reported that gender differences may result from production objectives and the specific roles and responsibilities of males and females in traditional livestock rearing. This is linked to the constant state of change, evolution and development of traditional gender roles (Paudel et al 2009;Karmebäck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The current study underscores the importance of adaptation traits like disease resistance and recognises that these traits are equally or more important than production traits. The findings from this study are in line with those of previous studies in Ethiopia by and recently in Somalia by Marshall et al (2016). It is therefore important to note that a critical understanding of the adaptation traits and including them in the breeding goal is vital for developing sustainable improvement programs.…”
Section: Farmer Preferred Trait Rankingsupporting
confidence: 89%
“…The most important of these included domestic milk consumption, income from the sale of milk, slaughter animals and breeding animals, savings and insurance, domestic meat consumption, transport and load carrying, drawing water from wells, ceremony and dowry and hide use (Marshall et al 2014). The livestock trait preferences of, and selection criteria used by, the pastoralists also varied by pastoralist gender and livestock species, but aligned well with the harsh environment under which the animals perform, the pastoral livestock-keeping objectives and the market requirements (Marshall et al 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Although strengthening the livestock sector is considered to be the key to poverty reduction and increased food security in Somalia (FAO 2010), few studies have reported the livestock management practices of Somali livestock keepers, including on breeding issues. So as to help address this knowledge gap, we have recently documented the livestock-keeping objectives, trait preferences of, and selection criteria used by, women and men pastoralists in Somaliland (located in north-western Somalia), for goats, sheep, cattle and camel (Marshall et al 2014(Marshall et al , 2016. The livestock-keeping objectives varied by gender of the pastoralist as well as livestock species; however, all species were kept for multiple objectives.…”
Section: Introductionmentioning
confidence: 99%